Matter, Freedom and the Future: Reframing Feminist Theologies through an Ecological Materialist Lens1 - Elvey, Anne F. (Feminist theology, 2015)
An ecological focus is not simply an additional perspective to add to a multidimensional approach to feminist theologies. Ecological thinking requires a fundamental shift of perspective, so that the focus of feminism, traditionally a human focus, is rethought within the frame of the materiality that constitutes not only humans but Earth and cosmos. As a way of situating feminist theological discourses and experiences ecologically, this article focuses on a shared materiality as a basis for reframing human being, dwelling, agency and labour, in terms of co-being, habitat, co-agency and more-than-human labour. This reframing implies a rethinking of human freedom that has implications for how we engage with feminist theologies in relation to the future of Earth and humankind.